2016
DOI: 10.1016/j.chb.2016.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Wearable technologies: The role of usefulness and visibility in smartwatch adoption

Abstract: Although still in the early stages of diffusion, smartwatches represent the most popular type of wearable devices. Yet, little is known about why some people are more likely to adopt smartwatches than others. To deepen the understanding of underlying factors prompting adoption behavior, the authors develop a theoretical model grounded in technology acceptance and social psychology literatures. Empirical results reveal perceived usefulness and visibility as important factors that drive adoption intention, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
355
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 419 publications
(392 citation statements)
references
References 70 publications
27
355
0
10
Order By: Relevance
“…Therefore, it was proved to impact satisfaction of mobile banking users' attitudes positively. Next factors were found to be perceived usefulness and ease of use, which were also consistent with the previous research (Bidar et al, 2014;Chuah, 2016). This finding revealed that users adopted mobile banking and became satisfied with it when mobile banking service technology was perceived as more useful than traditional banking services and the usage of this service was easy.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, it was proved to impact satisfaction of mobile banking users' attitudes positively. Next factors were found to be perceived usefulness and ease of use, which were also consistent with the previous research (Bidar et al, 2014;Chuah, 2016). This finding revealed that users adopted mobile banking and became satisfied with it when mobile banking service technology was perceived as more useful than traditional banking services and the usage of this service was easy.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research finds out that perceived usefulness has a positive effect on continuance intention to use e-government (Hamid et al, 2016), intentions to buy halal-labelled products (Jamal & Sharifuddin, 2015), mobile banking adoption (Al-Jabri & Sohail, 2012), and attitude toward using smartwatches and adoption intention (Chuah et al, 2016). According to TAM, it is assumed that perceived usefulness and perceived ease of use are two key factors that determine the decision of consumer ijms.ccsenet.org International Journal of Marketing Studies Vol.…”
Section: Innovation Characteristics and Innovation Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experience might change the results such that certain dimensions’ impact increases or decreases. Prior research has tested this assumption and does not conclude crucial effects (e.g., Chuah et al., ). However, as price points decline and new apps come on the market, gratifications and their influence on consumers might change.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research studies have focused predominately on accuracy and reliability issues (Canhoto & Arp, ; Chuah et al, ), as well as design, aesthetic and implementation issues (Choi & Kim, ; Kim, Park, & Choi, ; Nieroda et al, ). In this study, we aim to bridge a research gap by understanding the effects of WTD adoption and explain consumers' intentions to use wearable devices as a means to manage their personal health.…”
Section: Introductionmentioning
confidence: 99%